PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN KOMPETENSI PEGAWAI PAJAK TERHADAP KEPUASAN WAJIB PAJAK - Rembet, Ariel; Karamoy, Herman; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Taxpayer satisfaction is very important in forming a positive view of the tax authorities. Starting with satisfaction, the taxpeyer does not feel aggrieved when paying taxes. It is also expected that with this satisfaction, the taxpayer will voluntarity pay taxes. The purpose of this study is to register the tax administration system and the tax competency of tax operators on the manado pratama tax service office. This study uses a quantitative approach, collection methods data is carried out through questionnaires. The sample of this study was 100 respondents, which was accidental sampling. Data analysis using statistical tech niques such as vallyditi test, reliability test for questionnaire. Besides the classic assumption test, multiple linear regression, determination coefficient for proof of hypothesis. The results show that the modernization of tax administration systems and the competence of tax employees simultaneously have a significant effect on taxpayer satisfaction. Partially from the results of tasting the test of modernization of the tax administration system and the competence of tax employees have a significant effect on taxpayaer satisfaction. The results of this study suggest that employees and all parties related to the tax service office manado tax service office must pay attention to the Â factors of the modern tax administration system and tax employees competence. Quality services from tax employees can make taxes feel comfortable and satisfied to fulfill their obligations to pay taxes.Keywords : Modenization of tax administration system, tax employee competence, taxpayer satisfaction.